Genetic conservation of Brazilian fishes - Present state and perspectives - Wasko, Adriane P. [UNESP]; Martins, Cesar [UNESP]; Oliveira, Claudio [UNESP]; Forest, Fausto [UNESP] (UNESP - Universidade Estadual Paulista, 2004)
Natural environments have been worldwide affected by the growing impact of anthropogenic actions that promote the reduction or the extinction of several vertebrate species. Aquatic ecosystems represent one of the most affected environments and many fish species and/or populations have been increasingly fragmented distributed due to habitat degradation, predatory fishing, introduction of exotic species, river sedimentation, deforestation, pollution, reduction of food resource, and construction of hydroelectric dams. Actually, more than 150 Brazilian fish species, including freshwater, estuary and coastal species, can be considered threatened. Information on the diversity, conservation biology and population analysis on threatened species or populations, with several DNA markers, can be extremely useful for the success of fish species-recovery and maintenance programs. Although DNA analysis in Neotropical fish species are just beginning, they tend to increase with the widespread attention to the use of molecular approaches to minimize problems related to the risk of extinction. The accumulation of information on biology and pattern of genetic variation of fish species, associated with ecological and demographic data, and also education and respect to the nature, constitutes a crucial task to develop efficient conservation strategies in order to preserve the genetic diversity in aquatic environments.
Keywords: Conservation genetics; Endangered species; Fish; Molecular markers; DNA; DNA marker; molecular marker; aquatic environment; Brazil; coastal waters; deforestation; degradation; demography; DNA determination; ecology; education; estuary; exotic species; fish; fishing; food; freshwater environment; genetic conservation; genetic variability; habitat fragmentation; natural science; nonhuman; population abundance; population dynamics; predation; review; river basin; river ecosystem; sedimentation; species conservation; species diversity; species extinction; vertebrate; water pollution; Pisces; Vertebrata